2009
DOI: 10.1111/j.1399-3038.2008.00753.x
|View full text |Cite
|
Sign up to set email alerts
|

Antineuronal antibodies and electroneurophysiological studies in pediatric patients with neuropsychiatric systemic lupus erythematosus

Abstract: Neuropsychiatric systemic lupus erythematosus (NPSLE) is one of the most difficult manifestations of lupus to diagnose. Measurement of serum brain autoantibodies and assessment of cognitive function by electroneurophysiological studies (electroencephalogram (EEG) and P300) have contributed to an earlier and a more specific diagnosis of NPSLE. Thus, we were stimulated to assess the value of serum antineuronal antibodies and electroneurophysiological studies in diagnosis and early prediction of NPSLE. To investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 21 publications
1
15
0
8
Order By: Relevance
“…The same can be said about anti-neuronal nuclear antibodies (ANNA). How et al [17][18][19][20] had reported that ANNA antibodies were strongly associated with NP manifestations in SLE. In our study, the incidence of true anti-neuronal antibodies after absorption of ANNA showed no statistically significant difference the incidence of Rib-P antibodies between NPSLE and SLE patients without neuropsychiatric involvement.…”
Section: Discussionmentioning
confidence: 97%
“…The same can be said about anti-neuronal nuclear antibodies (ANNA). How et al [17][18][19][20] had reported that ANNA antibodies were strongly associated with NP manifestations in SLE. In our study, the incidence of true anti-neuronal antibodies after absorption of ANNA showed no statistically significant difference the incidence of Rib-P antibodies between NPSLE and SLE patients without neuropsychiatric involvement.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, with P300 testing, damage of cognitive functions resulting from taking different medicines, especially antiepileptic drugs, can also be monitored (61)(62)(63). Additionally, P300 characteristics help diagnosing cognitive damage resulting from systemic diseases, such as anaemia, uremia (renal insufficiency), hepatic encephalopathy, systemic lupus erythematosus, diabetes mellitus, hypothyreosis, as well as COPD (64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76). Moreover, cognitive function damage in patients with HIV-1 neurologically asymptomatic seropositive can be assessed with P300 testing (78).…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive damage in some systemic diseases can be assessed with CEP P300 (64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78). Improvements in the treatment and recovery can be followed in the same way.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Subsequent studies determining their clinical utility to detect cNPSLE have, however, been mixed; some studies report that serum antineuronal antibodies in adults with lupus are neither sensitive nor specific [84,85], making them poor biomarkers in either the detection of disease or in confirming that disease is primary cNPSLE. In the few studies in pediatrics, there are also mixed findings in regards to an association between cNPSLE and serum antineuronal antibodies [86–88], but little data concerning CSF antibodies. In general, it appears that CSF antineuronal antibodies have improved sensitivity and specificity compared with serum antibodies and there may be little utility in these as a marker from peripheral blood [82,89].…”
Section: Experimental Biomarkersmentioning
confidence: 99%